Efek Emotional Freedom Technique dan Deep Breathing Exercise terhadap Penurunan Kecemasan Pasien - Lailaturohmah Kurniawati; Andri Setiya Wahyudi; Sriyono Sriyono (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effect of Emotional Freedom Technique Therapy (EFT) and deep breathing exercises to reduce patient anxiety. The method used is a literature review of the Scopus, ScienceDirect, Proquest, Sage and Ebsco databases. The results showed that 14 articles proved that EFT therapy and deep breathing exercise reduced patient anxiety and were influential in combination with other relaxation therapies. In conclusion, EFT therapy and deep breathing exercises have a significant effect in reducing patient anxiety. Keywords: Anxiety, Deep Breathing Exercise, EFT